Well-designed nanosheet-constructed porous CoMoS4 arrays for ultrahigh-performance supercapacitors. Issue 4 (March 2020) - Xu, Xiaoyang; Liu, Qianqian; Liang, Linan; Gu, Haoran; Zhao, Ying; Xing, Xuteng; Zhang, Xiangjing; Hu, Yongqi
Abstract: Nanosheet-constructed porous CoMoS4 arrays are grown on 3D self-supported Ni foam by a simple solvothermal strategy. The resulting sample can be immediately served as an adhesive-free electrode of supercapacitors. Surprisingly, the obtained CoMoS4 /Ni foam with high chemical activity and unique structure exhibits excellent performance including the high specific capacity of 276 mAh/g at 0.25 A/g. Moreover, the prepared CoMoS4 /Ni foam and commercial activated carbon (AC) are specified as the positive/negative electrodes of a hybrid supercapacitor. The assembled CoMoS4 /Ni foam//AC hybrid device outputs a high specific energy of 58 Wh/kg at a specific power of 328 W/kg, and 95% of initial capacity after 10, 000 charge-discharge cycles. These conditions are favorable for the practical application of the prepared CoMoS4 /Ni foam. Therefore, the nanosheet-constructed porous CoMoS4 arrays on Ni foam can be considered as a hopeful electrode for energy storage devices.